An algal lectin griffithsin inhibits Hantaan virus infection in vitro and in vivo - Zhao, Yajing; Zhao, Ningbo; Cai, Yanxing; Zhang, Hui; Li, Jia; Liu, Jiaqi; Ye, Chuantao; Wang, Yuan; Dang, Yamei; Li, Wanying; Liu, He; Zhang, Lianqing; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Hantaan virus (HTNV) is the etiological pathogen of hemorrhagic fever with renal syndrome in East Asia. There are currently no effective therapeutics approved for HTNV and other hantavirus infections. We found that griffithsin (GRFT), an algae-derived lectin with broad-spectrum antiviral activity against various enveloped viruses, can inhibit the growth and spread of HTNV. In vitro experiments using recombinant vesicular stomatitis virus (rVSV) with HTNV glycoproteins as a model revealed that the GRFT inhibited the entry of rVSV-HTNV-G into host cells. In addition, we demonstrated that GRFT prevented authentic HTNV infection in vitro by binding to the viral N-glycans. In vivo experiments showed that GRFT partially protected the suckling mice from death induced by intracranial exposure to HTNV. These results demonstrated that GRFT can be a promising agent for inhibiting HTNV infection.